The effect of intellectual capital on financial performance of manufacturing companies listed in Indonesia Stock Exchange period 2007-2011 - Dea Nikki Rona; Luciana Spica Almilia (STIE Perbanas Surabaya, 2013)
The purpose of this study is to empirically examine the influence of intellectual capitalproxied by human capital, structural capital, and physical capital which can affect thecompanys financial performances measured by return on equity (ROE), earning pershare (EPS), and operational profit margin (OPM). The population of this research iscompanies listed in Indonesia Stock Exchange period 2007-2011 and meet the criteriafor the samples in this study. The sample selection is using purposive samplingmethod and obtained 60 companies as the samples. The results are as follow: intellectualcapital (VAICTM) significantly affects the financial performance of the return onequity (ROE) and operational profit margin (OPM) variables reinforced the companysmodest size, while the intellectual capital (VAICTM) has no affect on earningper share (EPS).